An integrated approach for top-corrected Ginis - Charlotte Bartels; Maria Metzing (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
Household survey data provide a rich information set on income, household context and demographic variables, but tend to under report incomes at the very top of the distribution. Administrative data like tax records offer more precise information on top incomes, but at the expense of household context details and incomes of non-filers at the bottom of the distribution. We combine the benefits of the two data sources and develop an integrated approach for top-corrected Gini coefficients where we impute top incomes in survey data using information on top income distribution from tax data. We apply our approach to European EU-SILC survey data which in some countries include administrative data. We find higher inequality in those European countries that exclusively rely (Germany, UK) or have relied (Spain) on interviews for the provision of EU-SILC survey data as compared to countries that use administrative data.
Keywords: C46; C81; D31; H2; 330; Gini coefficient; Top income shares; Survey data; Tax record data; Pareto distribution